Introduction to the Special Issue on the Gulf of San Jorge (Patagonia, Argentina) - St-Onge, Guillaume (2018)
San Jorge Gulf (SJG) is home to a complex ecosystem that provides a variety ofhigh-quality services to the regional andnational economy of Argentina, particularly oil and gas, fisheries, and tourism.The gulf is located in the central region ofPatagonia between 45°S and 47°S, coversan area of 39,340 km2, and is open to theAtlantic Ocean. Until recently, althoughsome interdisciplinary scientific information had been gathered for the SJG,very little had been published in widelyaccessible journals. This special issue ofOceanography aims to document fundamental research into SJG biological,physical, chemical, and sedimentary processes undertaken in the last few years.More than 40 researchers, students, andtechnicians from Québec (Canada) andArgentina participated in the initialefforts of PROMESse (Multidisciplinaryprogram for the study of the ecosystemand geology of the San Jorge Gulf and thecoastal region of the province of Chubut),which closely matches the Argentineangovernment?s Pampa Azul Initiative.The general objective of the PROMESseresearch program is to conduct an integrated study of the SJG, with the resultsserving as a baseline for the sustainablemanagement of the ecosystem services ofthis rich marine ecosystem. This bilateraleffort included two workshops, held in2017, one in Rimouski (Québec, Canada)and another in Comodoro Rivadavia(Chubut, Argentina), that led to the15 articles published in this special issue.